The Kantian Moral Hazard Argument for religious fictionalism - Jay, Christopher (International journal for philosophy of religion, 2014)
In this paper I do three things. Firstly, I defend the view that in his most familiar arguments about morality and the theological postulates, the arguments which appeal to the epistemological doctrines of the first Critique, Kant is as much of a fictionalist as anybody not working explicitly with that conceptual apparatus could be: his notion of faith as subjectively and not objectively grounded is precisely what fictionalists are concerned with in their talk of nondoxastic attitudes. Secondly, I reconstruct a logically distinct argument to a fictionalist conclusion which I argue Kant also gives us, this time an argument to the conclusion that it is a good thing if our commitment to the existence of God is nondoxastic. And finally, I argue that this argument is of continuing interest, to Kantians and non-Kantians alike, not only because it raises interesting questions about the relation of morality to belief in God (which go in the opposite direction to most discussions, which focus on whether and to what extent belief in God can be an aid to morality), but also because this ‘Moral Hazard Argument’ seems to be available to religious realists and non-realists alike, thus suggesting that religious fictionalism is not by any means just an interesting version of religious non-realism.